PERANCANGAN CO-WORKING SPACE DENGAN PENERAPAN FLEKSIBILITAS RUANG DI KOTA YOGYAKARTA - Faisal, Muhammad; Saud, Mohammad Ibnu (UNIVERSITAS LAMBUNG MANGKURAT, 2023)
Creative economy has become an integral part of the global economy today. In Indonesia, particularly in the city of Yogyakarta, the creative industry and economy are experiencing rapid growth, especially in the startup sector. However, many startup entrepreneurs face challenges in having their own offices and choose to work from places such as homes, cafes, or rented accommodations to develop their businesses. This is mainly due to the high cost of office rentals, long lease terms, and limited flexibility. In this context, Co-working Spaces are considered an ideal solution because they offer affordable rental costs and are accessible to various types of businesses. Furthermore, Co-working Spaces should provide a conducive environment for various activities in the digital creative economy, particularly in the context of startup business development. Therefore, there is a need to design a Co-working Space in Yogyakarta that offers a high level of spatial flexibility to facilitate collaboration and networking among industry players. The design incorporates the concept of spatial flexibility using the superimposition method, where architectural elements that form the space are separated and rearranged randomly to create three types of relationships: reciprocity, disregard, and contradiction. These three relationships are implemented to achieve optimal spatial flexibility and address the challenges in designing a Co-working Space in Yogyakarta.